EVALUASI FORMATIF BAHAN AJAR FISIKA DASAR 1 - Tuti Purwoningsih (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Instructional materials should meet both criteria of grammar used and in terms of legibility, so the (Subject Matter Book) SMB easy to read and digest, using simple language, communicative and clear. This study aims to collect data and information that is specific and detailed than SMB Physics 1 to revise the SMB to fit the learning strategically applying the principles of independent learning. Model development of teaching materials used in this study is the Model Instructional Design for Distance Education by Michael Simonson, (2012) that adaption from The Systematic Design of Instruction by Dick, Carey and Carey (2009).                              The results showed that SMB Physics 1 should be revised because of the competence to be achieved are still lower student or high school level. Level of achievement and qualifications BMP Physics of the results of the Review are still low material experts are 1) the suitability of the material to be achieved student competencies; 2) breadth of materials for physics education courses; 3) The depth of the material for physical education courses; 4) clarity of illustration, examples and non-examples; and 5) the attractiveness of illustrations, examples and non-examples.Keywords: formative evaluation, teaching materials, teaching strategies, Physics 1.